2020
DOI: 10.1088/1402-4896/ab68bd
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen trapping in tungsten: impact of helium irradiation and thermal cycling

Abstract: The impact of helium (He) plasma exposure with He fluxes relevant for ITER and WEST on the near-surface microstructure of polycrystalline tungsten (W) is investigated by coupling transmission electron microscopy (TEM) analysis and thermal desorption spectrometry (TDS) measurements. The samples were exposed in the PSI-2 linear plasma device to 75 eV He ions up to the fluence of 3 × 10 23 He m −2 with the surface temperature in the range 1053-1073 K. The obtained He bubbles-enriched W samples are subsequently pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
6
19
0
Order By: Relevance
“…When the cluster is over-pressurised, additional Frenkel pairs will be created. He bubbles can then form in W and their morphology depends on the exposure conditions 4 7 . Such bubbles have been observed using Molecular Dynamics (MD) 3 , 8 – 12 and Object Kinetic Monte Carlo 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the cluster is over-pressurised, additional Frenkel pairs will be created. He bubbles can then form in W and their morphology depends on the exposure conditions 4 7 . Such bubbles have been observed using Molecular Dynamics (MD) 3 , 8 – 12 and Object Kinetic Monte Carlo 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, when over-pressurised bubbles are close to the surface, bursting can occur as shown by Sefta et al in MD simulations 12 , 19 . Bursting greatly modifies surface morphologies by increasing the roughness and producing craters 4 and W-fuzz 7 , 20 23 . Moreover, He exposure can alter H retention in W 4 , 24 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) simulations show that a large amount of H can be accommodated around He bubbles [16,10,17]. Increased D retention was observed experimentally in a recent study after thermal cycling of He irradiated W samples where visible bubbles were observed [18]. Increased D retention was found experimentally also in keV-range ion beam experiments [19,20] which seems to be in contradiction to what was observed in mixed He-D plasma exposures.…”
Section: Introductionmentioning
confidence: 89%
“…In this contribution D retention and transport is studied in He-implanted and self-damaged W by exposing it to D atoms at 600 K with atom energy of 0.28 eV and flux of about 3.5×10 18 D/m 2 s.…”
Section: Introductionmentioning
confidence: 99%